HERMENEUTICS PERSPECTIVE OF THE WORD ‘MEN” IN THE DECLARATION OF INDEPENDENCE - Rosyid Dodiyanto; Ade Christanty Yudha Bestari (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2023)
Abstract The aims of this research are to reveal the meaning of “men” inside the text of the Declaration of Independence and to explain the hermeneutics perspective inside the meaning of the text. This research is based on descriptive qualitative analysis. The writer describes the facts of American Women demonstrating their movement in struggling their rights through American Congress found in the primary sources. In doing this, the writer uses hermeneutic as a tool to analyze the texts. The result of this research is to prove that gender problems related to language. It can be seen that in 1920 American women really started their independence after 144 years America had its independence from the tyranny of Great Britain. Keywords: The Declaration of Independence, hermeneutics perspective, and American Women.